Analysis of the Effectiveness of Disbursement and Efficiency of Zakat and Alms Fund Management at the Zakat Amil Institution (LAZ) of Zakat Sukses - Khairiah, Nadyatul; Bahri, Efri Syamsul (Indo Consultan Energi, 2025)
This study aims to analyze the effectiveness and efficiency of zakat disbursement and management, as well as the management of infaq/sadaqah funds at the Zakat Amil Zakat Institution (LAZ) and Zakat Sukses. This study uses a quantitative method. Effectiveness is analyzed using the Allocation to Collection Ratio (ACR) formula. Furthermore, efficiency is analyzed using Data Envelopment Analysis (DEA). Data were obtained from LAZ Zakat Sukses in the form of Financial Reports and Annual Reports of Zakat Sukses for the period 2018-2022. The results of the study indicate that the effectiveness of zakat and infaq/sadaqah distribution, with an average value of 91% is in the very effective category. Furthermore, the efficiency of zakat and infaq/sadaqah fund distribution, with an average of 99.26%, is in the increasing category. LAZ Zakat Sukses needs to maintain and improve the effectiveness and efficiency of zakat and infaq/sadaqah distribution to ensure the objectives of zakat management are achieved.